Attitudes of health professionals towards suicidal behavior: an intervention study - Jesiele Spindler Faria; Samira Reschetti Marcon; Alice Milani Nespollo; Hugo Gedeon Barros dos Santos; Mariano Martínez Espinosa; Kleici Kleslly Brito de Oliveira; Josemara Gomes da Silva Lima (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To evaluate the effect of an educational intervention on the attitudes of primary healthcare providers regarding patients with suicidal behavior. METHODS Clinical trial randomized by clusters, with a sample of 261 healthcare professionals, from 22 health units selected by stratified sampling, were chosen and randomly allocated, by drawing, into two groups: intervention (n = 87) and control (n = 174). The participants of the intervention group were exposed to a 20-hour training on suicidal behavior. All 261 participants were evaluated before and after the intervention; the groups were compared to evaluate their attitude towards suicidal behavior using the Suicide Behavior Attitude Questionnaire (SBAQ), an evaluation made by comparison of the means via t-Student test, for independent samples, and paired t-test, for dependent samples. RESULTS The intervention group, in comparison to their evaluation before and after training, as well as in the comparison with the evaluation of the control group, showed statistically significant differences in attitudes towards suicidal behavior, according to the differences presented in the scores for the domains: "perception of professional capacity," in all four items; "negative feeling," in six of the seven items; and in the "right to commit suicide" domain, in three of the five items. CONCLUSION The brief training developed in primary health care was effective to improve the attitudes of the participants who were part of the intervention group regarding patients with suicidal behavior.